Investigating the causal impact of gut microbiota on trigeminal neuralgia: a bidirectional Mendelian randomization study - Zeng, Chuan; Zhang, Chaolong; Jia, Yuxuan; Zhou, Huaiyu; He, Chunming; Song, Haimin (Frontiers in Microbiology, 2025)
BackgroundThe etiology and pathogenesis of trigeminal neuralgia remain unclear. This study examines the connection between gut microbiota and trigeminal neuralgia using Mendelian randomization analysis to provide insights into the disorder’s origin and propose potential therapies based on our findings.MethodsWe used data from the MiBioGen consortium (13,266 participants) for gut microbiota and the IEU OpenGWAS project (800 cases, 195,047 controls) for trigeminal neuralgia. We checked for heterogeneity and horizontal pleiotropy and used the inverse variance weighting method as our main approach to study the causal link between gut bacteria and trigeminal neuralgia, MR-Egger, simple mode, weighted median, and weighted mode as supplementary methods, with a sensitivity test using leave-one-out analysis. If a bacteria-trigeminal neuralgia link was found, we conducted a reverse analysis for confirmation.ResultsAccording to the final results, these groups include Butyricimonas (Genus, id = 945, p-value = 0.007, OR = 1.742, 95% CI: 1.165–2.604), unknowngenus (Genus, id = 1000005479, p-value = 0.005, OR = 1.774, 95% CI: 1.187–2.651) and Bacteroidales (Family, p-value = 0.005, OR = 1.774, 95% CI: 1.187–2.651) were causally associated with trigeminal neuralgia. No significant results according to reverse Mendelian randomization analysis.ConclusionIn our study, we identified specific gut bacteria linked to trigeminal neuralgia. To comprehensively understand their impact and mechanisms, additional randomized trials are necessary.